2019
DOI: 10.2471/blt.19.230128
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the provision of analgesia during childbirth, Japan

Abstract: Japan’s universal health-care system means that it is a very safe country in which to give birth. Perinatal outcomes in Japan are excellent, with low infant mortality and neonatal mortality. However, childbirth remains a challenge for many Japanese women, who are faced with a scarcity of places to give birth, limited availability of analgesia and social norms that favour natural birth. The number of birth facilities in Japan continues to decrease as fewer children are born. The numbers of qualified medical sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…28 Analgesia is rarely used for routine vaginal births in the public health system in the focus countries assessed here, as is the case in many Asian countries. 30 Future studies to examine these factors in detail in the East Asia and Pacific region may be warranted. In addition, this study did not include preterm babies who were not the focus of EENC until after 2017.…”
Section: Strengths and Weaknesses Of The Studymentioning
confidence: 99%
“…28 Analgesia is rarely used for routine vaginal births in the public health system in the focus countries assessed here, as is the case in many Asian countries. 30 Future studies to examine these factors in detail in the East Asia and Pacific region may be warranted. In addition, this study did not include preterm babies who were not the focus of EENC until after 2017.…”
Section: Strengths and Weaknesses Of The Studymentioning
confidence: 99%
“…The choice of EDA can be influenced by different factors, including cultural beliefs-as labor pain is considered a virtue in Japan, the rate of analgesic delivery in Japan is very low, at the level of 6.2% in 2016. The low rate of labor analgesia in Japan is also influenced by the difficulties in access to birth facilities and shortage of anesthesiologists [12]. Shishido et al found Decision Aids (algorithms prepared to facilitate the decision about EDA in labor) useful in assisting informed decision making, and found a significant increase in patient's satisfaction with their choice when compared to a group of women who received only informative pamphlets [13].…”
Section: Discussionmentioning
confidence: 99%
“…An example of this cultural difference is that women in Japan are less likely to have an epidural in labor compared with American women. 26 The MHS provides universal health care coverage regardless of education or economic status. This population may be ideal to study how socioeconomic status plays into opioid prescription patterns.…”
Section: Discussionmentioning
confidence: 99%